Thomas' Calculus 13th Edition

Published by Pearson
ISBN 10: 0-32187-896-5
ISBN 13: 978-0-32187-896-0

Chapter 1: Functions - Section 1.2 - Combining Functions; Shifting and Scaling Graphs - Exercises 1.2: 7

Answer

$(f\circ g\circ h)(x)=-3x+13$

Work Step by Step

We are given $f(x)=x+1$, $g(x)=3x$, and $h(x)=4-x$. So $(f\circ g\circ h)(x)=f(g(h(x)))=f(g(4-x))=f(3(4-x))=3(4-x)+1\\=12-3x+1=-3x+13$.
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.